Tanda dan Makna Wacana dalam Poster Kampanye Pencegahan Kekerasan Seksual Menggunakan Teori Semiotika C.S Peirce - Zulfa, Salma Rizqiya; Ruhendi, Aceng; Harras, Kholid Abdul (Sasdaya: Gadjah Mada Journal of Humanities, 2025)
Sexual violence is one of the most talked about cases in society, especially in Indonesia. Many victims are reluctant to report cases of sexual violence due to a lack of evidence or psychological barriers arising from fear, shame, and public ridicule. Because of the rampant cases of sexual violence, several artists were moved to carry out a campaign to prevent sexual violence by making an educational poster. The purpose of this research is to analyze the semiotic signs and meanings in the sexual violence prevention posters more profoundly and to deepen the responses from the responders regarding the posters that have been uploaded. This research uses descriptive and qualitative research design. The data used in this research is from a sample of 13 posters from 9 posts on Instagram. The results and discussion in this study found that icons in this study contain figurative meanings and use many female icons. Meanwhile, symbols in this study are in the form of descriptive information. The index in this study describes many negative images representing the victim's condition. Interpretants in this study found responders' comments that approved the poster information. This research implies that it is suitable to be a reference for linguistic and visual communication research.